2014
DOI: 10.1007/s12275-014-4112-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in CYP51B from Penicillium digitatum involved in prochloraz resistance

Abstract: Green mold caused by Penicillium digitatum is one of the most serious postharvest diseases of citrus fruit, and it is ubiquitous in all citrus growing regions in the world. Sterol 14α-demethylase (CYP51) is one of the key enzymes of sterol biosynthesis in the biological kingdom and a prime target of antifungal drugs. Mutations in CYP51s have been found to be correlated with resistance to azole fungicides in many fungal species. To investigate the mechanism of resistance to prochloraz (PRC) in P. digitatum, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…Thus a potential debate on real function of MATE family member(s) in citrus Penicillium pathogens' resistance to DMIfungicides would be an interesting study topic. Over-expression of ERG11s, the P450-dependent sterol 14α-demethylase (CYP51)-encoding genes (e.g., CYP51A/ B/C), has been accepted as a primary strategy to develop fungal DMI-resistance [9,27,33]. Under prochloraz induction, the increasing fold of CYP51A in Pi-R (~9-fold) was more than that in Pi-S (~4.5-fold) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus a potential debate on real function of MATE family member(s) in citrus Penicillium pathogens' resistance to DMIfungicides would be an interesting study topic. Over-expression of ERG11s, the P450-dependent sterol 14α-demethylase (CYP51)-encoding genes (e.g., CYP51A/ B/C), has been accepted as a primary strategy to develop fungal DMI-resistance [9,27,33]. Under prochloraz induction, the increasing fold of CYP51A in Pi-R (~9-fold) was more than that in Pi-S (~4.5-fold) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The site mutations in CYP51s (ERG11-encoding proteins) can alter drug-target interactions and increase DMI-resistance for various fungal pathogens, as reported in the model yeast Saccharomyces cerevisiae [14][15][16], the clinical pathogens Candida albicans [17][18][19][20] and Aspergillus fumigatus [21][22][23], and the plant pathogens Mycosphaerella graminicola [24,25], Monilinia fructicola [26] and P. digitatum [27]. Fungal resistance to DMIs can also be ascribed to overexpression of CYP51s, especially by some enhancer elements [9,[27][28][29][30][31][32][33]. In addition to CYP51s, recently, other genes encoding fungal ergosterol biosynthesis-related enzymes have been proposed to be potential targets, including ERG2 (encoding C − 8 sterol isomerase) [34][35][36] and ERG6 (encoding C − 24 sterol methyltransferase) [37][38][39][40].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…These showed that the F495I mutation in A. fumigatus corresponds to F506I in P. digitatum and F489L in P. teres. It has been suggested that the F506I mutation plays an important role in the structure and function of Cyp51 and contributes to prochloraz resistance in P. digitatum strains from China (22). This mutation was found in combination with G459S mutation (22).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the F506I mutation plays an important role in the structure and function of Cyp51 and contributes to prochloraz resistance in P. digitatum strains from China (22). This mutation was found in combination with G459S mutation (22). F489L mutation in P. teres has also been shown to be associated with a high level of prochloraz resistance, and further structural in silico modeling analysis showed that interaction of F489L with the heme cavity produced a localized constriction of the region adjacent to the docking site that is predicted to result in lower binding affinities (22).…”
Section: Discussionmentioning
confidence: 99%
“…Demethylase inhibitors (DMIs) have been exploited as azole-antifungal drugs to inhibit lanosterol 14α-demethylase (CYP51), impairing ergosterol/lanosterol metabolisms and finally resulting in fungal growth inhibition [5]. DMI fungicides have been widely used in medicine and agriculture, but the resistance to DMIs has been reported in many fungal species [6,7]. It is imperative to design new and efficient fungicides for the treatment of pathogens of plants based on the CYP51 structure.…”
Section: Introductionmentioning
confidence: 99%